THE QUALITY OF SPERM AND FEMALE AGE AS FACTORS INFLUENCING PREGNANCY IN INTRACYTOPLASMIC SPERM INJECTION (ICSI) - Hadibrata, Exsa; Utomo, Trisula (Indonesian Journal of Urology, 2020)
Objective: To evaluate the quality of sperm and the female age influence on fertilization and pregnancy rate after Intracytoplasmic Sperm Injection (ICSI) procedure. Material & Methods: This study was an observational analytic study with a retrospective cohort design. The data of infertile and subfertile male undergoing ICSI for five years were analyzed and evaluated to determine factors influencing pregnancy post-ICSI in Central General Hospital Dr. Sardjito. The Data were analyzed by using Chi-squared test, Kolmogorov-Smirnov test, and Mann-Whitney U test with the confidence level of p<0.05 and α=0.05. Results: There was 52 male included in this study. A total of 52 males were infertile, with azoospermia, oligozoospermia, and oligoasthenoteratozoospermia. 2 patients (3.8%) were patients with oligozoospermia, 32 patients (61.5%) were patients with azoospermia and 18 patients (34.6%) were patients with oligoasthenoteratozoospermia. We evaluated 52 ICSI cycle, the percentage of fertilization and pregnancy are 84.6% and 36.5%, respectively. Bivariate analysis showed a significant relationship between wife under 37 years old variable and pregnancy post ICSI procedure with p=0.021 and OR 9.0 (95% CI 1.05-76.4). There was no significant difference between azoospermia, oligozoospermia, and oligoasthenoteratozoospermia and the occurrence of pregnancy post ICSI procedure, p=0.986. Conclusion: The percentage of fertilization and pregnancy post ICSI procedure were 84.6% and 36.5%. Azoospermia, oligozoospermia, and oligoasthenoteratozoospermia variables were not significantly associated with pregnancy post ICSI procedure. ICSI procedure must be carried out immediately before the age of the wife 37 years because of the high success rate.